2016
DOI: 10.24017/science.2016.1.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating e-Government Services in Kurdistan Institution for Strategic Studies and Scientific Research Using the EGOVSAT Model

Abstract: Abstract:Office automation is an initiative used to digitally deliver services to citizens, private and public sectors. It is used to digitally collect, store, create, and manipulate office information as a need of accomplishing basic tasks. Azya Office Automation has been implemented as a pilot project in Kurdistan Institution for Strategic Studies and Scientific Research (KISSR) since 2013. The efficiency of governance in Kurdistan Institution for Strategic Studies and Scientific Research has been improved, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
2
2
2
Order By: Relevance
“…This study supports previous research by Herlina et al [10], which shows that Customization has no significant effect on user satisfaction. On the other hand, this study does not support previous research conducted by Horan and Abhichandani [3], Alias et al [5] and Ahmed et al [4], who found that Customization had a significant positive effect on user satisfaction.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This study supports previous research by Herlina et al [10], which shows that Customization has no significant effect on user satisfaction. On the other hand, this study does not support previous research conducted by Horan and Abhichandani [3], Alias et al [5] and Ahmed et al [4], who found that Customization had a significant positive effect on user satisfaction.…”
Section: Discussioncontrasting
confidence: 99%
“…It means that the higher the efficiency, the higher the user satisfaction with the Malang City Online Tax Application. This study supports the results of research conducted by Horan and Abhichandani [3], Alias et al [5] and Ahmed et al [4].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations